A Survey of Neo-Babylonian History - Von Voigtlander, Elizabeth Nation
Ph.D.; University Microfilms Order No. 64-8220. Microfilm $3.55: Xerography $12.40; Dissertation Abstracts 25/3 (Ann Arbor, Mich., September 1964) 1867-1868.